ESG growth catalyst: China's Central Bank collateral framework expansion. - Xupei Wang; Liang Zhao (PLoS ONE)
Environmental, social, and governance (ESG) plays an important role in corporate sustainability. In June 2018, the People's Bank of China (China's central bank) decided to expand the scope of the Medium-Term Lending Facility (MLF) collateral to include green bonds issued by companies. This study investigates the impact of the PBOC's policy of integrating green bonds into the collateral framework on corporate ESG performance, specifically by alleviating financing constraints and fostering green innovation. Specifically, this study takes the Expanded Pledge Framework Policy (EPCF) of the Central Bank as a quasi-natural experiment and uses the panel data of China's A-share listed companies from 2014 to 2022 to investigate the causal relationship between EPCF and corporate ESG performance through the differential method (DID) and other methods. The results show that EPCF can improve the ESG performance of enterprises by easing the financing constraints of enterprises and promoting the green technology innovation of enterprises. On average, implementing an EPCF improves the relative ESG performance of an organization by about 0.02 units. In addition, through the parallel trend test and the results of existing literature, it can be seen that although enterprises issuing green bonds can improve ESG performance, the range is still limited, and EPCF has a greater improvement in the ESG performance of non-heavy polluting enterprises. More importantly, the implementation of EPCF is more effective in regions with a higher degree of marketization and in coastal areas. Our model has withstood extensive robustness checks.